2015
DOI: 10.1007/s00056-015-0285-5
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health in teenagers treated with removable aligners and fixed orthodontic appliances

Abstract: Teenagers treated with removable appliances display better compliance with oral hygiene, less plaque, and fewer gingival inflammatory reactions than their peers with fixed appliances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 24 publications
4
102
0
8
Order By: Relevance
“…However, few studies have addressed changes in the microbiota and periodontal health in relation to clear aligner treatments. It has always been known that patients using clear aligners are less likely to suffer F I G U R E 2 Rarefaction curves for the salivary community before treatment and after 6-month Invisalign treatment [Colour figure can be viewed at wileyonlinelibrary.com] more serious periodontal diseases either in a short time or in the long term than patients with fixed appliances (Abbate, Caria, & Montanari, 2015;Lu, Tang, Zhou, & Kang, 2018;Rossini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have addressed changes in the microbiota and periodontal health in relation to clear aligner treatments. It has always been known that patients using clear aligners are less likely to suffer F I G U R E 2 Rarefaction curves for the salivary community before treatment and after 6-month Invisalign treatment [Colour figure can be viewed at wileyonlinelibrary.com] more serious periodontal diseases either in a short time or in the long term than patients with fixed appliances (Abbate, Caria, & Montanari, 2015;Lu, Tang, Zhou, & Kang, 2018;Rossini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Abbate et al [18] revealed the microbiological and periodontal changes that may occur during orthodontic treatment; comparing aligners and fixed appliances, they found that aligners were associated with greater compliance, better oral hygiene, less accumulation of plaque, and less gingival inflammation than fixed appliances. These findings are in line with those reported in a previous study by Mietheke et al [19], and in another that showed an increase in periodontopathic bacteria associated with a worsening of periodontal health in fixed multibracket orthodontics with respect to aligners [20].…”
Section: Discussionmentioning
confidence: 99%
“…It was noted that changes such as caries can appear after 4 weeks from the start of orthodontic treatment. 19,20 It has been shown that the presence of braces causes changes in the saliva and thus leads to disturbances in the oral environment. It was proven that patients with orthodontic appliances have higher concentrations of bacteria in the mouth, changes in the buffer capacity, pH, and the speed of saliva secretion.…”
Section: Local Complications Associated With the Use Of Bracesmentioning
confidence: 99%
“…On the other hand, it increases surface retention of plaque, which favors the growth of bacteria and the formation of gingivitis. 19,21 A study by Kasacka et al has shown significant changes in the morphology of epithelial cells of the oral mucosa of patients with braces. 22 These changes were even more marked in patients with braces and amalgam fillings.…”
Section: Local Complications Associated With the Use Of Bracesmentioning
confidence: 99%